Pengaruh Kualitas Pelayanan Terhadap Kepuasan Konsumen Di PT. Tiki Jalur Nugraha Ekakurir Cabang Kawaluyaan Bandung - Kiki Andriyana; Ramadani Kurnia Dewi; Rita Zulbetti (Ekonomis: Journal of Economics and Business, 2021)
The purpose of this study was to determine the magnitude of the effect of service quality on customer satisfaction at PT. Tiki Jalur Nugraha Ekakurir Kawaluyaan Branch Bandung. The method used is quantitative method. The data collection technique was carried out by distributing questionnaires to 28,587 visitors with a set sample of 100 respondents with reference to the calculation of the Slovin formula. This data was then processed using SPSS V 25. The data analysis technique used was simple linear regression and also correlation. The results showed that there was a strong relationship between the services provided and customer satisfaction. This is shown by statistical tests (validity test, correlation coefficient test, coefficient of determination test and hypothesis testing). The t-test shows that there is an influence between service quality and customer satisfaction with a t-value of 16,377 evidence strengthened by the calculation of the coefficient of determination of 67%.